The Role of Governance on Supporting Corporate Social Responsibility Le Rôle De La Gouvernance Dans Le Soutien à La Responsabilité Sociale Des Entreprises - Bellakhdar, Abdelkader (Finance and Business Economies Review, 2019)
The aim of the study was to try to address the issue of corporate governance and its role in supporting social responsibility efforts by presenting the most important foundations of governance in improving the performance of the institution in general. The study concluded that governance plays an important role in supporting social responsibility through a number of fundamental aspects, namely encouraging institutions to play a more visible and appropriate role in their external environment, contributing to the achievement of sustainable development requirements, and strengthening the relationship of the institution with its customers in particular and all actors parties in general.